ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PRODUKSI PEMBENIHAN IKAN LELE DUMBO (Clarias gariepenus) DI KABUPATEN WONOGIRI - M. Djoko Pramono; Endang Siti Rahayu; Minar Ferichani (Universitas Muhammadiyah Semarang, 2017)
This research are for: (1) To analysis the cost and income of Catfish hatchery farm in Wonogiri District. (2) To analysis the influence factors of Catfish hatchery production in Wonogiri District. (3) To analysis the efficiency level of feed production, natural food, and labour. The basic method of the research is description analysis method and the conduct of the research is using a census method. This research had conducted in the district of Wonogiri which consist of 45 respondents, analyzed data included hatchery income, R/C ratio, elasticity, efficiency, and multiple linier regression test. The result of the research showed that the relation between factors and hatchery of Dumbo Catfish production showed in multiple linier regression model, they are : LnP = 7.472 - 0.047LnX1 + 0.312LnX2 + 0.388LnX3 + 0.304LnX4 + 0.136LnX5 + 0.016LnX6 + 0.108LnD1 + 0.058LnD2. The result of the analysis showed the number of broodstock, feed, natural food, labour, hatchery technology and counseling which were significant influenced in Catfish hatchery production, meanwhile the land area and hatchery process were not really influences to the Catfish hatchery production. The result of the research had obtained the income of Catfish hatchery with the price of Rp. 2.369.533,-, value of R/C ratio was 2,67, feed production value, natural food, and labour were >1 which showed inefficient, the elasticity value of all independent variable was elastic. Keywords: Income, efficiency production, the Factors of Hatchery Production.